Comparative Study in Physical Fitness in Recreative Young Padel Players - Ana Pereira; Luis Leitão; Diogo L. Marques; Daniel A. Marinho; Henrique P. Neiva (Journal of Functional Morphology and Kinesiology, 2025)
Background: In recent years, padel-based interventions have been widely applied in junior and elite players of both genders concerning athletic performance, whereas evidence of their efficacy in trials that use simple randomization has not been well established. This study aimed to compare the effects of 8 weeks of padel training (PD) on the strength and power of untrained healthy children. Methods: Twenty-five children aged 11–15 years (12.36 ± 1.15 years) were randomly assigned into experimental (PD) (nine boys and five girls: 1.58 ± 0.04 m; 50.00 ± 6.75 kg; and 19.96 ± 1.95 kg/m2) and control (CT) (seven boys and four girls: 1.60 ± 0.05 m; 56.92 ± 2.75 kg; and 21.61 ± 1.02 kg/m2) groups. The PD group trained twice a week for 8 weeks, and the CT group did not follow any training program and did not participate in regular exercise or sports. Countermovement jump, medicine ball throw, handgrip, and 5 m sprint test results were measured at baseline and after the intervention in the padel sport group. Results: The results showed a significant interaction for training-induced responses in the sprint test (T5) (F = 10.55, p = 0.004, η2 = 0.31). No significant interactions were observed for handgrip strength (HG) (F = 3.90, p=0.06), the medicine ball throw (MBT) (F = 0.851, p = 0.37, η2 = 0.04), and the countermovement jump (F = 1.04, p =0.32, η2 = 0.04), with clear improvements from pre- to post-training in the PD group. After 8 weeks of training, the PD group showed increased performance in handgrip strength (p = 0.004), while the CT group had decreased velocity post-training (p = 0.011). Conclusions: The individual results in the PD group showed an improvement, which suggests that the practice of padel seems to be a good strategy for improving one’s fitness. It is suggested that 8 weeks of PD seem to be effective in improving strength- and power-related variables in healthy, untrained children. This could be considered an alternative to traditional sports to improve the body fitness of young children and should be applied in school-based programs and the sports club community. Also, more high-quality RCTs are needed in the future.